Impact of Insurance Coverage on Outcomes in Primary Breast Sarcoma. (15th March 2018) - Koenig, Julie L.; Tsai, C. Jillian; Sborov, Katherine; Horst, Kathleen C.; Pollom, Erqi L.
Abstract : Private insurance is associated with better outcomes in multiple common cancers. We hypothesized that insurance status would significantly impact outcomes in primary breast sarcoma (PBS) due to the additional challenges of diagnosing and coordinating specialized care for a rare cancer. Using the National Cancer Database, we identified adult females diagnosed with PBS between 2004 and 2013. The influence of insurance status on overall survival (OS) was evaluated using the Kaplan–Meier estimator with log-rank tests and Cox proportional hazard models. Among a cohort of 607 patients, 67 (11.0%) had Medicaid, 217 (35.7%) had Medicare, and 323 (53.2%) had private insurance. Compared to privately insured patients, Medicaid patients were more likely to present with larger tumors and have their first surgical procedure further after diagnosis. Treatment was similar between patients with comparable disease stage. In multivariate analysis, Medicaid (hazard ratio (HR), 2.47; 95% confidence interval (CI), 1.62–3.77;p < 0.001 ) and Medicare (HR, 1.68; 95% CI, 1.10–2.57;p = 0.017 ) were independently associated with worse OS. Medicaid insurance coverage negatively impacted survival compared to private insurance more in breast sarcoma than in breast carcinoma (interactionp < 0.001 ). In conclusion, patients with Medicaid insurance present with later stage disease and have worse overall survival than privately insured patients with PBS. Worse outcomes for Medicaid patients are exacerbated in this rare cancer.